The effect of reciprocal teaching learning model assisted by resitation on student learning otcomes - Bafadal, Rifqi; Sukardi, Sukardi; Nursaptini, Nursaptini (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This research aims to analyze whether or not there is an effect of reciprocal teaching learning model assisted by resitation on students' learning outcomes. The population in this research is all students of class XI IPS SMAN 10 Mataram, whose samples are taken randomly after class matching. The approach used is quantitative with quasi experiment research type with pretest - posttest control group design. The collection of information using multiple option tests that have met the provisions of instrument testing. Information analysis uses descriptive statistics. There is also a test of information requirements tested using the normality test and homogeneity test. The results of this research show that there is an effect of the reciprocal teaching learning model assisted by resitation on learning outcomes with a significance value of 0.028 < 5% (0.05). The N-Gain score test results prove that the experimental class has a greater value than the control class as measured by cognitive aspects C1, C2, C3, C4, C5. The theoretical implication is that the use of this model strengthens the learning theory, especially the constructivistic theory.